Implementing the teaching factory model in English language instruction: Students' perceptions and learning strategies - Cahyaningati, Desi Tri; Puspandari, Lusia Eni; Utari, Dian Asa; Miftachudin, Miftachudin (Journal of Applied Studies in Language, 2024)
Many vocational schools have been bringing their educational practice closer to industry along with the concept of Teaching Factory (TEFA) to adjust the students’ skills as close as the industry demands. The implementation of TEFA based curriculum in one of vocational higher education in Surabaya for all subjects including English subject has been performed since 2019. In English classes, the Teaching Factory-Based Strategy covers two methods: product-based learning and flipped classroom. This research aims to explore the implementation of TEFA-based strategy and the two methods by revealing students' perceptions and responses on the strategy. This research is descriptive qualitative research in which data were obtained through questionnaires and interviews. The students observed were from 4 different study programs in this PPNS. The results of this study show positive perceptions of students toward TEFA – based strategy implemented in the classroom even though there are some obstacles faced by both students and lecturers. Hopefully this research can contribute practically to English teachers who are adopting TEFA in English language teaching.